A door is to open - Maclear, Kyo, 1970- (Tundra, 2026)
"Embrace your curiosity in this meditative, moving and visually stunning picture book that celebrates doorways, thresholds and portals, and the endless possibilities they contain. With evocative, thought-provoking prose and gorgeous mixed media artwork, A Door is to Open is a collaboration from award-winning author and illustrator duo Kyo Maclear and Julie Morstad that will spark imaginations and encourage fresh perspectives with readers of all ages. A deceptively simple invitation to venture out into the world, this picture book offering will resonate with anyone entering a new phase of life or needs a little burst of inspiration to try something new."--